2000
DOI: 10.1074/jbc.m003439200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gαi Palmitoylation by Activation of the 5-Hydroxytryptamine-1A Receptor

Abstract: Nearly all ␣ subunits of heterotrimeric GTP-binding regulatory proteins (G proteins) are palmitoylated at cysteine residues near the N terminus. A regulated cycle of palmitoylation could provide a mechanism for modulating G protein signaling by affecting protein interactions and localization of the subunit. In the present studies we utilized both Heterotrimeric guanine nucleotide-binding regulatory proteins (G proteins) 1 transduce signals from cell-surface receptors to intracellular effectors via multiple p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 67 publications
3
19
0
Order By: Relevance
“…The basis for this variation is unclear, particularly since Loisel et al (41) have suggested that repalmitoylation of the depalmitoylated ␤ 2 -adrenoreceptor-G␣ s fusion protein is inhibited and that this might be related to the poor capacity of this construct to become desensitized. Interestingly, however, we have observed that agonist also greatly accelerates the kinetics of acylation of a 5-hydroxytryptamine 1A-receptor-G␣ o1 fusion protein, 2 consistent with observations of an enhanced rate of [ 3 H]palmitoylation of G␣ i when activated by a co-expressed 5-hydroxytryptamine 1A receptor (42).…”
Section: Discussionsupporting
confidence: 70%
“…The basis for this variation is unclear, particularly since Loisel et al (41) have suggested that repalmitoylation of the depalmitoylated ␤ 2 -adrenoreceptor-G␣ s fusion protein is inhibited and that this might be related to the poor capacity of this construct to become desensitized. Interestingly, however, we have observed that agonist also greatly accelerates the kinetics of acylation of a 5-hydroxytryptamine 1A-receptor-G␣ o1 fusion protein, 2 consistent with observations of an enhanced rate of [ 3 H]palmitoylation of G␣ i when activated by a co-expressed 5-hydroxytryptamine 1A receptor (42).…”
Section: Discussionsupporting
confidence: 70%
“…The co-distribution of PAT and its substrates in lipid rafts would facilitate repalmitoylation. Agonists stimulate palmitate turnover on G ␣s and G ␣i , and this may have a regulatory role in desensitization of G-protein responses (43)(44)(45)(46). In vitro, palmitoylated G ␣i is resistant to deactivation by RGS proteins (47).…”
Section: Discussionmentioning
confidence: 99%
“…Shuttling and Translocation Are Inhibited by 2BP-The G protein ␣ subunits belonging to the G i/o , G s , and G q families are palmitoylated (5), and the palmitoyl moiety can be turned over in the basal deactivated state (t1 ⁄ 2 Ͼ 60 min for ␣ i ; 90 min for ␣ s ) (23)(24)(25). We tested whether acylation played a role in the shuttling of G protein subunits and the translocation of the ␤␥ complex between PM and endomembranes by examining the effect of 2BP, an inhibitor that has been used for identifying palmitoylation (13) of proteins.…”
Section: G Protein Shuttling Is Likely Diffusion-mediated-mentioning
confidence: 99%